Enhancing Reflective Teaching Practices: Implications for Faculty Development Programs - Hubball, Harry; Collins, John; Pratt, Daniel (Canadian Journal of Higher Education, 2005)
Reflecting on one’s teaching practice is often an implicit goal for faculty development programs. Yet very little has been documented how programs for diverse groups of university teachers actually engage faculty in such reflection. This paper examines how theoretical constructs of reflective practice were applied in the context of an 8-month UBC Faculty Certificate Program on Teaching and Learning in Higher Education (FCP). The Teaching Perspectives Inventory (TPI) was particularly useful for providing faculty cohort members with a means of looking more deeply at the underlying values and assumptions that constituted their philosophical orientations to teaching. Furthermore, a change in faculty members’ TPI scores indicate that participants reflected more comprehensively on their teaching at the end of the program, than they did at the beginning of the program. Barriers to facilitating reflection included inadequate time allocation, unclear expectations and goals for reflection activities, and varying cultural norms for reflective teaching practices within academe.